Regressive Myocardial Infarction with ST Elevation (STEMI) Treated with Conservative Medicinal Therapy - Alexis Karaky; Snezhanka Tisheva-Gospodinova (Journal of Biomedical & Clinical Research)
The case presented is that of a young man with atypical pathogenesis of myocardial infarction with ST-elevation (STEMI) after physical stress. It was provoked by partial thrombosis of the distal segment of the left main coronary artery (LM) at the bifurcation of the left anterior descending artery. After the emergency treatment, the disease process underwent reverse development without any consequences for left ventricular kinetics.